Chemical Reaction and Mhd Flow for Magnetic Field Effect on Heat and Mass Transfer of Fluid Flow Through a Porous Medium Onto a Moving Vertical Plate - B. Shankar Goud; Mahantesh M. Nandeppanavar (International Journal of Applied Mechanics and Engineering, 2022)
This article discusses the effect of heat and mass transfer in a boundary layer flow in the presence of a magnetic field of an electrically conducting and viscous fluid as it passes through a porous medium containing a heat source and a chemical reaction. By employing similarity variables, the governing equations are changed into nonlinear ordinary differential equations(ODEs). To solve the obtained equations numerically the Keller box method is used. Numerical and graphical representations of the results of different parameter values governing the flow system are given. The non-dimensional distributions of velocity, heat, and concentration are depicted graphically, while the Nusselt number, Sherwood number, and skin friction are determined numerically.